Effectiveness and utilization of a cognitive screening program for primary geriatric care - David P. Salmon; Anna Malkina; Melanie L. Johnson; Christina Gigliotti; Emily A. Little; Douglas Galasko (Alzheimer’s Research & Therapy)
Abstract Background Effective detection of cognitive impairment in the primary care setting is limited by lack of time and specialized expertise to conduct detailed objective cognitive testing and few well-validated cognitive screening instruments that can be administered and evaluated quickly without expert supervision. We therefore developed a model cognitive screening program to provide relatively brief, objective assessment of a geriatric patient’s memory and other cognitive abilities in cases where the primary care physician suspects but is unsure of the presence of a deficit. Methods Referred patients were tested during a 40-min session by a psychometrist or trained nurse in the clinic on a brief battery of neuropsychological tests that assessed multiple cognitive domains. Short questionnaires covering subjective cognitive complaints, symptoms of depression, and medical history were also administered. Results were conveyed to a dementia specialist who reviewed them and returned their judgement of the validity of the cognitive complaint to the primary care provider. Retrospective medical records review was carried out for a random (stratified) half of the sample to determine how screening results were utilized. Screening tests were repeated after two years in a subset of 69 patients. Results The 638 patients screened (mean age = 75.9 years; mean education = 14.9 years; 58% women) were classified by screening as having normal cognition (n = 177), depression (with possible cognitive changes; n = 115), mild cognitive impairment (MCI; n = 107), or dementia (n = 239). Classification accuracy was shown by high agreement with the eventual clinical diagnosis in the medical record (69%; Cohen’s Kappa = .38; p < .001; 77% if MCI and dementia were collapsed; Cohen’s Kappa = .58; p < .001) and longitudinal decline in cognitive test scores only in those initially classified as having MCI or dementia. Medical records documented discussion of screening results with the patient in 69% of cases (80% if MCI or dementia was detected) and often referral to a specialist (62%), new brain imaging (54%), or change in medication (58%) when screening indicated potential cognitive impairment. Conclusion The cognitive screening program was well accepted by primary care providers as an efficient and effective way to evaluate concerns about cognitive decline in older adults.